Reel Time: Movie Exhibitors and Movie Audiences in Prairie Canada, 1896 to 1986 - Robert M. Seiler and Tamara P. Seiler (Athabasca University Press, 2013)
In this authoritative work, Seiler and Seiler argues that the establishment and development of moviegoing and movie exhibition in Prairie Canada is best understood in the context of changing late-nineteenth-century and early-twentieth-century social, economic, and technological developments. From the first entrepreneurs who attempted to lure customers in to movie exhibition halls, to the digital revolution and its impact on moviegoing, Reel Time highlights the pivotal role of amusement venues in shaping the leisure activities of working- and middle-class people across North America. As marketing efforts, the lavish interiors of the movie palace and the romantic view of the local movie theatre concealed a competitive environment in which producers, exhibitors, and distributors tried to monopolize the industry and drive their rivals out of business. The pitched battles and power struggles between national movie theatre chains took place at the same time that movie exhibitors launched campaigns to reassure moviegoers that theatres were no longer the